Experimental implementation controlled SPWM inverter based harmony search algorithm - Najeeb M.; Mansor M.; Razali R.; Daniyal H.; Yahaya J.A.F. (International Journal of Renewable Energy Research, 2023)
C (programming language); Controllers; Electric inverters; Errors; Learning algorithms; MATLAB; Particle swarm optimization (PSO); Pulse width modulation; Voltage control; And transient response; C code for the sine PWM; C++ codes; Ezdsp f28335 board; Harmony search algorithm; Harmony search algorithms; Mean absolute error; Pulse width modulation inverters; Sinusoidal pulsewidth modulations (SPWM); Transient analysis